1997
DOI: 10.1097/00000542-199701000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cricoid Cartilage Pressure Decreases Lower Esophageal Sphincter Tone

Abstract: These findings may explain the occurrence of pulmonary aspiration before tracheal intubation despite application of cricoid cartilage pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 17 publications
1
42
2
5
Order By: Relevance
“…2 This technique has become the cornerstone of rapid sequence induction of anesthesia. Although the efficacy and hence the necessity of this maneuver has been questioned, 3,4 its use continues to be recommended by airway guideline developers. In a recent editorial, Dr. Lerman points out that ''currently, there is insufficient evidence to advocate or abandon the use of cricoid pressure to prevent passive regurgitation in at-risk anesthetized patients.''.…”
Section: Résumémentioning
confidence: 99%
“…2 This technique has become the cornerstone of rapid sequence induction of anesthesia. Although the efficacy and hence the necessity of this maneuver has been questioned, 3,4 its use continues to be recommended by airway guideline developers. In a recent editorial, Dr. Lerman points out that ''currently, there is insufficient evidence to advocate or abandon the use of cricoid pressure to prevent passive regurgitation in at-risk anesthetized patients.''.…”
Section: Résumémentioning
confidence: 99%
“…No entanto, durante o vômito, quando a pressão esofágica pode ser superior a 60 cmH 2 O, a manobra deve ser suspensa, pois pode haver ruptura esofágica. A compressão da cartilagem cricóide aumenta o tônus do esfíncter esofágico superior 14 , mas diminui o do inferior 15 , o que sugere a presença de mecanorreceptores na faringe que promoveriam relaxamento reflexo desse esfíncter. Esse efeito, porém, parece não provocar refluxo gastroesofágico 16 .…”
Section: Pressão Intragástricaunclassified
“…However, during vomiting, when esophageal pressure can be higher than 60 cmH 2 O, the maneuver should be discontinued due to the risk of esophageal rupture. Applying pressure on the cricoid cartilage increases the tonus of the upper esophageal sphincter 14 , but decreases the tonus of the lower esophageal sphincter 15 , suggesting the presence of mechanoreceptors in the pharynx that promote relaxation of this sphincter. However, this effect does not seem to cause gastroesophageal reflux 16 .…”
Section: Intragastric Pressurementioning
confidence: 99%
“…Salem et al further demonstrated that application of cricoid pressure during bag mask ventilation in pediatric patients prevents gastric inflation and thus also help in preventing regurgitation and aspiration [3] . The efficacy of cricoid pressure in prevention of aspiration has been doubted in the last 20 years and has been questioned by clinicians, with few suggesting abandoning this maneuver altogether [4,5] . Anecdotal case reports of regurgitation despite cricoid pressure being applied incited the debate whether cricoid pressure is really effective or just a 55 year old ritual [6] .…”
Section: Introductionmentioning
confidence: 99%